Reasons for Using Interurban Bus Transport - Malić, Adolf; Stiperski, Zoran; Kovačević, Dražen (Promet - Traffic&Transportation, 2012)
The authors analyse the reasons for using the interurban bustransport in Croatia based on a swvey carried out in 1996, on asample of 2,293 passengers. The respondents gave reasons fortaking the intentrban bus. The results indicate that the mainreason for taking the bus are going to or returning from work.Other reasons included going to school, visiting relatives andadministrative obligations at the local district.